A Study of Place Making in Historical and Cultural Districts Driven by Cultural Conservation - Zhang, Jingchi (MAJ - Malaysia Architectural Journal, 2025)
Historical and cultural districts are the concentrated display places of local culture, and cultural conservation activities are closely related to them. With the high-quality development of cultural tourism, place theory plays a vital role in place-making in historical and cultural districts. however, the difficult creation of identification hinders the development of the spirit of place. so the research question is if cultural conservation activities inspire participants to create the spirit of place at the fixed and open spaces in the historical and cultural districts. It is based on place theory and conducts mixed methods research through literature review, questionnaire, field investigation and interview. Firstly, it analyzes the different types of cultural conservation activities in historical and cultural districts and the different spaces that are generated. Secondly, it innovatively puts forward the argument that creating the fixed and open cultural conservation activity space in historical and cultural districts as a miniature urban living room can empower the districts, which is distinguished from cultural display space and urban living room. Then, the paper analyses the existing structure of cultural conservation organizations in China and takes Chongqing Cultural Conservation Corps as an example to explain its core driving force, analyses the behaviors change of tourists: learning, protecting, and communicating in the transformation process, and clarifies the important role of fixed and open space, story-driven and interactive activities that ultimately lead visitors from a one-off tour to the local attachment to the historical and cultural districts. This research aims to reshape the space vitality of historical and cultural districts and revive the space charm, so as to achieve the purpose of improving place experience and enriching the spirit of place.